Expansion of the secondary range of Polygraphus proximus Blandford (Coleoptera; Curculionidae, Scolytinae): invasion of Khamar-Daban mountains (Republic of Buryatia) - Kerchev, Ivan; Bykov, Roman; Ilinsky Yury (Zenodo, 2023)
The four-eyed fir bark beetle Polygraphus proximus Blandford, 1894 (Coleoptera; Curculionidae, Scolytinae) is an alien Far-Eastern stem pest rapidly spreading in the dark coniferous forests of Siberia. In 2021 we conducted a forest pathology research of Khamar-Daban fir forests in south coast of Baikal Lake. The main aim was to inspect the territory for populations of this species. We found three localities with P. proximus on two out of four transects and based upon photo materials represented by stuff of the Baikal Nature Reserve revealed another locality inhabited by the species. The characteristics of P. proximus populations such as occurrence, production, population density and the population growth rate in new localities were estimated. Since of our previous forest pathological inspection in 2014 it had spread eastward in Baikal region by at least 95 km. The highest site of P. proximus population was the slope of the valley of the Bolshoi Mamai River at an altitude of 1030 m above sea level. The estimated average speed of spread was about of 13-14 km per year. However, the most presumable invasion pathway of this species is the Trans-Siberian Railway. Thus, genetic analysis of sampled insects for the COI marker (mtDNA) revealed haplogroup I that previously was found as dominant variant in populations of Kemerovo and Tomsk Provinces. Despite the scattered distribution of P. proximus in Khamar-Daban fir forests the high population growth rate allows us to expect the formation of outbreaks during next decade. Ministry of Science and Higher Education of the Russian Federation, the grant No. 075-15-2020-787 for implementation of Major scientific projects on priority areas of scientific and technological development (the project "Fundamentals, methods and technologies for digital monitoring and forecasting of the environmental situation on the Baikal natural territory"